(untitled) (Hilo Analítico, 2022)
The Covid 19 pandemic, decreed in March by the World Health Organization (2020), given the concern about the high levels of spread of this disease in the world and the impact it has generated on health; It also forced psychology to follow unavoidable pro cesses that began in different countries, such as the death of many people, presenting general figures as of May (2021) of 157,124,615 infections; where 3,274,727 have died and 93,235,116 have recovered and in Colombia, there are 2,985,536 cases, 77,359 deaths and 2,806,310 people have recovered. This panorama presented, allowed to carry out this article whose objective was to know the process of mourning that families who have lost a loved one are experiencing, given the peculiar conditions, differential to the rites that generally occur in these cases of death of relatives, friends, neighbors and colleagues, where the ritual of death, given the sanitary conditions, does not allow a personalized accompaniment for the management of grief, given the health restrictions, not giving opportunities to generate a farewell This It forces psychology to generate care and intervention strategies for those who have had these losses, which can lead to disorders such as depression, anxiety and even suicidal behavior; Therefore, it was important to carry out a systematic review of scientific documents that allowed us to broaden our view of the process of mourning the death of a loved one in times of the pandemic generated by Covid 19.